Climate variability features of the last interglacial in the East Antarctic EPICA Dome C ice core. Issue 11 (6th June 2014) - Pol, K.; Masson‐Delmotte, V.; Cattani, O.; Debret, M.; Falourd, S.; Jouzel, J.; Landais, A.; Minster, B.; Mudelsee, M.; Schulz, M.; Stenni, B.
Abstract Whereas millennial to submillennial climate variability has been identified during the current interglacial period, past interglacial variability features remain poorly explored because of lacking data at sufficient temporal resolutions. Here we present new deuterium data from the EPICA Dome C ice core, documenting at decadal resolution temperature changes occurring over the East Antarctic plateau during the warmer‐than‐today last interglacial. Expanding previous evidence of instabilities during the last interglacial, multicentennial subevents are identified and labeled for the first time in a past interglacial context. A variance analysis further reveals two major climatic features. First, an increase in variability is detected prior to the glacial inception, as already observed at the end of Marine Isotopic Stage 11 in the same core. Second, the overall variance level is systematically higher during the last interglacial than during the current one, suggesting that a warmer East Antarctic climate may also be more variable.